Ensiklopedia Jawa Barat. - Lentera Abadi, PT. (Jakarta : Lentera Abadi, 2011)
Encyclopedia of West Java Province, Indonesia.
Includes bibliographical references and index.
Keywords: Jawa Barat (Indonesia) -- Encyclopedias